Technichal efficency of Francisco Sá Carneiro Airport: The potential impacts on region tourism - Dos-Santos, Maria José Palma Lampreia (2014)
The Oporto Airport is located in Porto city on the North of Portugal. This airport had an increasing in number of passengers, sales revenue and accumulated investment during the last two decades, principally after the introduction and the operation of the Low Cost Companies (LCCs) in 2004. In order to determine if these changes had an impact in the competitiveness of this airport, the main goal of this study is to measure the levels of technical efficiency during a time horizon 1990-2011 and compare these results before and after the introduction of the LCCs in this airport, and relate these efficiency levels to some potential consequences in tourism in Porto and North of Portugal. The methodology selected to measure the individual levels of efficiency was Data Envelopment Analysis (DEA). The inputs and outputs were selected according to referred authors in this subject area. Results show that the Oporto Airport efficiency increases highly after the introduction of LCCs. The paper confirmed the results obtained by others authors, namely, this airport has similar levels of efficiency as others international airports across the world, but more detailed and strong studies are necessary. The main conclusions suggest also the importance of the introduction of LCCs in the efficiency of the Oporto Airport and the potential relation with tourism development in this region, but further studies are needed.